2018
DOI: 10.1093/toxsci/kfy213
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Urinary Kidney MicroRNA Panel as Potential Nephron Segment-Specific Biomarkers of Subacute Renal Toxicity in Preclinical Rat Models

Abstract: Drug-induced kidney injury (DIKI) remains a significant concern during drug development. Whereas FDA-endorsed urinary protein biomarkers encounter limitations including the lack of translatability, there is a considerable interest surrounding the application of microRNAs (miRNAs) in the renal biomarker space. Current knowledge about the value of these novel biomarkers for subacute preclinical rodent studies is still sparse. In this work, Wistar rats were treated with three nephrotoxic compounds-cisplatin (CIS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Additional miRNAs were increased to a greater extent in urine from rats treated with TAL versus proximal tubule toxicants (eg,, which is in agreement with data from LCM experiments showing that these 2 latter miRNAs were overall preferentially enriched in the TAL and/or CD fractions versus the proximal tubules. Interestingly, miR-210-3p was clearly increased in urine from rats treated with TAL toxicants and was also previously reported to be increased in urine from rats treated with the CD toxicant NPAA (Glineur et al, 2018). This is in accordance with results from our localization experiments with LCM samples showing that miR-210-3p was enriched in the TAL and/or CD fractions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additional miRNAs were increased to a greater extent in urine from rats treated with TAL versus proximal tubule toxicants (eg,, which is in agreement with data from LCM experiments showing that these 2 latter miRNAs were overall preferentially enriched in the TAL and/or CD fractions versus the proximal tubules. Interestingly, miR-210-3p was clearly increased in urine from rats treated with TAL toxicants and was also previously reported to be increased in urine from rats treated with the CD toxicant NPAA (Glineur et al, 2018). This is in accordance with results from our localization experiments with LCM samples showing that miR-210-3p was enriched in the TAL and/or CD fractions.…”
Section: Discussionsupporting
confidence: 91%
“…Six miRNAs were found significantly increased in urine from rats treated with the CD toxicant NPAA in this study. On the other hand, Glineur et al (2018) reported that the expression profiles of 36 different urinary miRNAs were significantly altered in male Wistar rats treated with NPAA at 500 mg/kg/day for up to 28 days, with miR-210-3p displaying the most robust changes. These discrepancies may be explained at least in part by a higher susceptibility of Wistar rats to the kidney lesions induced by NPAA (Betton et al, 2012) as compared with SD rats which were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We then performed a detailed evaluation of each title and abstract and 1343 were excluded due to being other forms of AKI, miRNA studied in cells and tissues, review articles, conference abstracts or editorial/commentary, and book chapters. Finally, 35 articles were eligible for full‐text screening and we selected 21 for final analysis 12‐32 . The application of the screening process and selection criteria is summarized in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The numbers add up to more than 21 as three studies examined both humans and animals 21,24,27 . and there were multiple agents studied in two publications 13,15 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation